PERFORMANCE TESTING OF SEAWATER DISTILLATION EQUIPMENT USING SOLAR POWER TO PRODUCE FRESH WATER - Sepdianto; Kosasih, Khaecal Rabbil Izzati; Bakhri, Mohammad Samsul (Politeknik Negeri Semarang, 2025)
Design is a stage that involves several systematic stages, ranging from basic calculations to the performance test process. In the process of making distillation equipment, after the fabrication process, a process of testing the performance of the tool is required. Where is the performance test process to find out if the tool is in accordance with the calculations made in the previous process. This study aims to determine the quality of water resulting from distillation which includes, TDS, odor, pH, and salinity. The test method used in this study is experimental by conducting a performance test of a distillation device that utilizes sunlight for 5 days with 5 liters of water tested (1 liter per day continuously) starting from 08.00 to 17.00 by making observations every 1 hour. The results of the equipment test show that the quality of the water produced from the distillation equipment has met the standards of the Indonesian Ministry of Health. No.2 of 2023, while for the highest freshwater productivity per day of 287 ml and the lowest 204 and for the highest distillation equipment performance with an efficiency value of 94.18% and the lowest efficiency of 86.75%. Keywords: Distillation; Solar Power; Sea Water; Quality